Is there still a role for intraoperative enteroscopy in patients with obscure gastrointestinal bleeding? - Pedro Monsanto; Nuno Almeida; Clotilde Lérias; Pedro Figueiredo; Hermano Gouveia; Carlos Sofia (Revista Espanola de Enfermedades Digestivas)
Background: in 21st century, endoscopic study of the small intestine has undergone a revolution with capsule endoscopy and balloon-assisted enteroscopy. The difficulties and morbidity associated with intraoperative enteroscopy, the gold-standard in the 20th century, made this technique to be relegated to a second level. Aims: evaluate the actual role and assess the diagnostic and therapeutic value of intraoperative enteroscopy in patients with obscure gastrointestinal bleeding. Patients and methods: we conducted a retrospective study of 19 patients (11 males; mean age: 66.5 ± 15.3 years) submitted to 21 IOE procedures for obscure GI bleeding. Capsule endoscopy and double balloon enteroscopy had been performed in 10 and 5 patients, respectively. Results: with intraoperative enteroscopy a small bowel bleeding lesion was identified in 79% of patients and a gastrointestinal bleed-ing lesion in 94%. Small bowel findings included: angiodysplasia (n = 6), ulcers (n = 4), small bowel Dieulafoy's lesion (n = 2), bleed-ing from anastomotic vessels (n = 1), multiple cavernous hemangiomas (n = 1) and bleeding ectopic jejunal varices (n = 1). Agreement between capsule endoscopy and intraoperative enteroscopy was 70%. Endoscopic and/or surgical treatment was used in 77.8% of the patients with a positive finding on intraoperative enteroscopy, with a rebleeding rate of 21.4% in a mean 21-month follow-up period. Procedure-related mortality and postoperative complications have been 5 and 21%, respectively. Conclusions: intraoperative enteroscopy remains a valuable tool in selected patients with obscure GI bleeding, achieving a high diagnostic yield and allowing an endoscopic and/or surgical treatment in most of them. However, as an invasive procedure with relevant mortality and morbidity, a precise indication for its use is indispensable.